Fluxo espontâneo e capacidade de jogo: estudos atorais a partir de princípios do teatro-esporte e do match de improvisação - Ferreira, Brenno Jadvas Soares (2015)
This research aims to investigate the relevance of improvisation work to THEATRESPORTS and the MATCH OF IMPROVISATION in \'scenic training\' and in the actor s preparation, analyzing their components, execution dynamics and development that has been consolidating in Canada, Argentina and European countries as an artistic practice and not so much explored as a pedagogical-theatrical instrument. In Brazil, there are groups working with these practices, but in literature there are few academic researches on Theatresports and Match. Moreover, it has not so far made for Portuguese translations of Keith Johnstone s works. As base study structures about the importance of improvisation in actor training, the principles researched are Keith Johnstone s \"Theatresports\" and Gravel s and Leduc s \"Match of Improvisation\" as well as an experience based on Melodrama games as enhancers of GAME CAPABILITY and SPONTANEOUS FLOW of actors creations.